Prostate Cancer Detected by Choroidal Tumor and Complete Response to Hormonal Therapy: Case Report and Literature Review of 24 Patients With Choroidal Metastasis From Prostate Cancer - Toshihiko Matsuo MD, PhD; Takehiro Tanaka MD, PhD; Aya Nakamura MD, PhD; Koichiro Wada MD, PhD (SAGE Publishing, 2021)
Metastatic choroidal tumors derived from prostate cancer are rare. In this study, we report a patient who manifested a choroidal tumor as the initial presenting sign of prostate cancer and review 23 patients with choroidal metastasis of prostate cancer in the literature to answer a clinical question how the choroidal metastases would respond to hormonal therapy. A 73-year-old man presented with a choroidal tumor in the right eye. He was in good health and had no previous history except for current hemodialysis in 3 years due to chronic renal failure as a sequel to glomerulonephritis. With the diagnosis of a probable metastatic tumor, positron emission tomography was performed to disclose high-uptake sites in multiple bones, lymph nodes, and the prostate, together with multiple nodular lesions in bilateral lungs on computed tomography (CT) scan. Serum prostate-specific antigen (PSA) was elevated to 541 ng/mL, which supported prostate cancer as the primary site. He had degarelix injection, and the choroidal tumor resolved rapidly and became flat degeneration in a month. Prostate biopsy showed poorly differentiated adenocarcinoma, and he underwent surgical castration. He had no medication until 3 years later when he showed gradual increase of serum PSA up to 6.05 ng/mL and multiple bony metastases on CT scan. Bicalutamide, switched to enzalutamide and then to abiraterone, led to the undetectable level of serum PSA until the last visit with no relapse of the choroidal metastasis, 6.8 years after the initial visit. In the literature review of 24 patients with choroidal metastasis of prostate cancer, including this patient, 8 patients presented a choroidal tumor as the initial sign and the choroidal lesions mostly showed complete response to hormonal therapy. Among 13 patients who were frequently in the course of hormonal therapy, choroidal metastases showed complete or partial response to external beam radiation to the eye in 11 patients and episcleral plaque radiotherapy in 2 patients. In conclusion, metastatic choroidal tumors of prostate cancer would show good response to hormonal therapy when the therapy has not been initiated. Hormone-resistant choroidal metastases in the therapeutic course of prostate cancer could be managed successfully by external beam radiation to the eye.